A yttria partially stabilized zirconia ceramic target material, a method of making and use thereof
Patent Information
- Application Number
- CN202410497191.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-24
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2044-04-24
AI Technical Summary
[0005]目前在制备EB-PVD用陶瓷靶材时,只使用单一粒径的陶瓷粉体,当粉体粒径小时,压制的靶材过于紧密,形成很多闭气孔导致靶材在进行EB-PVD时容易产生喷溅;当粉体粒径大时,压制的靶材结合力不够,烧结以及进行EB-PVD时靶材容易出现开裂现象,影响涂层质量
[0024]本发明将两种不同粒径的陶瓷粉体进行混合,然后冷等静压压制和烧结,使得小粒径粉体夹于大粒径粉体中间,既增加了粉体的结合力,也使得靶材内闭气孔大大降低,提高了EB-PVD生产时的稳定性,无异象发生,使得涂层性能大大提高。
Smart Images

Figure CN118373684B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of thermal barrier coating preparation technology, and in particular to a yttrium oxide partially stabilized zirconia ceramic target, its preparation method, and its application. Background Technology
[0002] With the development of aviation, aerospace, and civilian technologies, the operating temperature requirements for hot-end components are becoming increasingly stringent, reaching the limits of high-temperature alloys and single-crystal materials. Taking the heated components of fuel turbines, such as nozzles, blades, and combustion chambers, as examples, they operate in harsh environments involving high-temperature oxidation and high-temperature airflow erosion, with temperatures reaching up to 1100℃, exceeding the operating temperature limit (1075℃) of high-temperature nickel alloys. Thermal barrier coatings, which combine the high strength and toughness of metals with the high-temperature resistance of ceramics, can solve these problems. They provide insulation, oxidation resistance, and corrosion protection, and have already been applied to hot-end materials in steam turbines, diesel generators, and jet engines, extending the service life of hot-end components.
[0003] Thermal barrier coatings not only improve corrosion resistance and further increase engine operating temperature, but also reduce fuel consumption (estimated to be nearly 20%) and extend the service life of hot-end components. Compared with developing new high-temperature alloy materials, the research and development cost of thermal barrier coating technology is much lower, and the process is also practically feasible. Therefore, thermal barrier coating technology has become the future development direction for high-temperature protective coating technology for engine hot-end components. In addition, thermal barrier coatings also have wide applications and research in hot-end components in shipbuilding, automobiles, energy, and other fields.
[0004] The preparation of thermal barrier coatings requires the use of EB-PVD (electron beam physical vapor deposition) technology. EB-PVD technology is an evaporation coating technology that uses a high-energy electron beam as a heat source. Specifically, in a vacuum environment, a high-energy ion beam bombards the target material, causing it to melt, sublimate, evaporate, and finally deposit on the substrate. The ceramic target material is the raw material for EB-PVD technology, and its performance will affect the performance and structure of the EB-PVD deposited coating.
[0005] Currently, when preparing ceramic targets for EB-PVD, only ceramic powder with a single particle size is used. When the powder particle size is small, the pressed target is too dense, forming many closed pores, which makes the target prone to splashing during EB-PVD. When the powder particle size is large, the pressed target has insufficient bonding force, and the target is prone to cracking during sintering and EB-PVD, affecting the coating quality. Summary of the Invention
[0006] The purpose of this invention is to provide a yttrium oxide partially stabilized zirconia ceramic target, its preparation method, and its application. The ceramic target prepared by this invention operates stably in EB-PVD, exhibiting no splashing and no cracking, thus significantly improving coating performance.
[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution:
[0008] This invention provides a method for preparing a yttrium oxide partially stabilized zirconia ceramic target, comprising the following steps:
[0009] The mixed powder of ZrO2 and Y2O3 was granulated to obtain a first ceramic powder and a second ceramic powder, respectively; the average particle size of the first ceramic powder was 5-50 μm; the average particle size of the second ceramic powder was 55-100 μm; and the difference between the average particle size of the second ceramic powder and the average particle size of the first ceramic powder was 50-80 μm.
[0010] The first ceramic powder and the second ceramic powder are mixed to obtain a multi-particle-size mixed powder;
[0011] The multi-size mixed powder is subjected to cold isostatic pressing to obtain a green body;
[0012] The green body is subjected to a first sintering to obtain a ceramic body;
[0013] The ceramic blank is subjected to a second sintering to obtain a yttrium-stabilized zirconia ceramic target.
[0014] Preferably, the mass ratio of the first ceramic powder to the second ceramic powder is (0.2-5):1.
[0015] Preferably, the mass of the ZrO2 is 92-94% of the total mass of ZrO2 and Y2O3.
[0016] Preferably, the pressure of the cold isostatic pressing is 30-200 MPa, and the holding time is 60-300 s.
[0017] Preferably, the first sintering includes: first heating to 400-800°C, first holding at that temperature for 6-10 hours, then heating to 1200-1600°C, second holding at that temperature for 6-10 hours, cooling down to 400-600°C, and finally cooling to room temperature with the furnace.
[0018] Preferably, the rates of the first and second heating are independently 50–100 °C / h; the rate of cooling is 50–100 °C / h.
[0019] Preferably, the second sintering temperature is 800–1200°C, and the holding time is 2–5 hours.
[0020] Preferably, before the second sintering, the ceramic blank is further subjected to mechanical processing.
[0021] The present invention provides a yttrium oxide partially stabilized zirconia ceramic target prepared by the preparation method described above.
[0022] This invention provides the application of the yttrium oxide partially stabilized zirconia ceramic target described above in the preparation of thermal barrier coatings by electron beam physical vapor deposition.
[0023] This invention provides a method for preparing a yttrium oxide partially stabilized zirconia ceramic target, comprising the following steps: granulating a mixed powder of ZrO2 and Y2O3 to obtain a first ceramic powder and a second ceramic powder; the average particle size of the first ceramic powder is 5-50 μm; the average particle size of the second ceramic powder is 55-100 μm; and the difference between the average particle size of the second ceramic powder and the average particle size of the first ceramic powder is 50-80 μm; mixing the first ceramic powder and the second ceramic powder to obtain a multi-grade mixed powder; cold isostatically pressing the multi-grade mixed powder to obtain a green body; performing a first sintering on the green body to obtain a ceramic body; and performing a second sintering on the ceramic body to obtain the yttrium oxide partially stabilized zirconia ceramic target.
[0024] This invention mixes two ceramic powders with different particle sizes, then cold isostatically presses and sintersects them, so that the smaller particle size powder is sandwiched between the larger particle size powder. This increases the bonding force of the powder and greatly reduces the closed pores in the target material, improving the stability of EB-PVD production, preventing abnormal phenomena, and greatly improving the coating performance. Attached Figure Description
[0025] Figure 1 This is a flowchart illustrating the preparation method of the yttrium oxide partially stabilized zirconia ceramic target of the present invention.
[0026] Figure 2 XRD pattern of the yttrium oxide partially stabilized zirconia ceramic target prepared in Example 1;
[0027] Figure 3 SEM image of the yttrium oxide partially stabilized zirconia ceramic target prepared in Example 1;
[0028] Figure 4 Photograph of the yttrium oxide partially stabilized zirconia ceramic target prepared in Example 1 after EB-PVD test;
[0029] Figure 5 XRD pattern of the yttrium oxide partially stabilized zirconia ceramic target prepared in Example 2;
[0030] Figure 6SEM image of the yttrium oxide partially stabilized zirconia ceramic target prepared in Example 2;
[0031] Figure 7 Photograph of the yttrium oxide partially stabilized zirconia ceramic target prepared in Example 2 after EB-PVD test;
[0032] Figure 8 XRD pattern of the yttrium oxide partially stabilized zirconia ceramic target prepared in Example 3;
[0033] Figure 9 SEM image of the yttrium oxide partially stabilized zirconia ceramic target prepared in Example 3;
[0034] Figure 10 Photographs of the yttrium oxide partially stabilized zirconia ceramic target prepared in Example 3 after EB-PVD testing;
[0035] Figure 11 SEM image of the yttrium oxide partially stabilized zirconia ceramic target prepared in Comparative Example 1;
[0036] Figure 12 Photograph of the yttrium oxide partially stabilized zirconia ceramic target prepared for Comparative Example 1 after EB-PVD test;
[0037] Figure 13 SEM image of the yttrium oxide partially stabilized zirconia ceramic target prepared in Comparative Example 2;
[0038] Figure 14 Photograph of the yttrium oxide partially stabilized zirconia ceramic target prepared for Comparative Example 2 after EB-PVD test. Detailed Implementation
[0039] This invention provides a method for preparing a yttrium oxide partially stabilized zirconia ceramic target, comprising the following steps:
[0040] The mixed powder of ZrO2 and Y2O3 was granulated to obtain a first ceramic powder and a second ceramic powder, respectively; the average particle size of the first ceramic powder was 5-50 μm; the average particle size of the second ceramic powder was 55-100 μm; and the difference between the average particle size of the second ceramic powder and the average particle size of the first ceramic powder was 50-80 μm.
[0041] The first ceramic powder and the second ceramic powder are mixed to obtain a multi-particle-size mixed powder;
[0042] The multi-size mixed powder is subjected to cold isostatic pressing to obtain a green body;
[0043] The green body is subjected to a first sintering to obtain a ceramic body;
[0044] The ceramic blank is subjected to a second sintering to obtain a yttrium-stabilized zirconia ceramic target.
[0045] Unless otherwise specified, all raw materials used in this invention are commercially available products well known in the art.
[0046] The present invention granulates a mixture of ZrO2 and Y2O3 powder to obtain a first ceramic powder and a second ceramic powder.
[0047] In this invention, the ZrO2 and Y2O3 mixed powder is preferably obtained by mixing ZrO2 and Y2O3; the purity of ZrO2 is preferably above 99%, and the purity of Y2O3 is preferably above 99%. In this invention, the mixing is preferably mechanical mixing, and the mixing time is preferably 5-10 hours. Before mixing, in this invention, ZrO2 and Y2O3 are preferably dried at 100-120°C for 6-12 hours to remove moisture from the powder.
[0048] In this invention, the mass of ZrO2 is preferably 92-94% of the total mass of ZrO2 and Y2O3, more preferably 92.5-93.5%.
[0049] In this invention, the granulation is preferably spray granulation. This invention does not have special requirements for the spray granulation process; any spray granulation process well-known in the art can be used. Preferably, this invention involves two spray granulation processes on the mixed powder to obtain a first ceramic powder and a second ceramic powder, respectively.
[0050] In this invention, the average particle size of the first ceramic powder is 5-50 μm, preferably 5-40 μm, more preferably 10-30 μm; the average particle size of the second ceramic powder is 55-100 μm, preferably 60-90 μm, more preferably 70-80 μm; the difference between the average particle size of the second ceramic powder and the average particle size of the first ceramic powder is 50-80 μm, specifically 50 μm, 60 μm, 70 μm or 80 μm.
[0051] After obtaining the first ceramic powder and the second ceramic powder, the present invention mixes the first ceramic powder and the second ceramic powder to obtain a multi-particle-size mixed powder.
[0052] In this invention, the mass ratio of the first ceramic powder to the second ceramic powder is preferably (0.2-5):1, more preferably (0.4-4):1, and even more preferably (1-3):1.
[0053] The present invention does not have special requirements for the mixing process, as long as the first ceramic powder and the second ceramic powder are mixed evenly.
[0054] After obtaining the multi-particle-size mixed powder, the present invention performs cold isostatic pressing on the multi-particle-size mixed powder to obtain a green body.
[0055] In this invention, the pressure of the cold isostatic pressing is preferably 30-200 MPa, more preferably 50-150 MPa, and even more preferably 70-120 MPa; the holding time of the cold isostatic pressing is preferably 60-300 s, more preferably 100-260 s, and even more preferably 140-220 s.
[0056] This invention uses cold isostatic pressing to compress multi-sized mixed powders into high-density material blanks.
[0057] After obtaining the green body, the present invention performs a first sintering on the green body to obtain a ceramic body.
[0058] In this invention, the first sintering preferably includes: first heating to 400-800°C, first holding at that temperature for 6-10 hours, then heating to 1200-1600°C, second holding at that temperature for 6-10 hours, cooling down to 400-600°C, and finally cooling to room temperature with the furnace.
[0059] In this invention, the rates of the first heating and the second heating are preferably 50-100°C / h, more preferably 60-90°C / h, and even more preferably 70-80°C / h; the rate of the cooling is preferably 50-100°C / h, more preferably 60-90°C / h, and even more preferably 70-80°C / h.
[0060] As a further preferred embodiment, the temperature after the first heating is more preferably 500-700℃, and most preferably 600℃; the first holding time is more preferably 7-9h, and most preferably 8h; the temperature after the second heating is more preferably 1300-1500℃, and most preferably 1400℃; the second holding time is more preferably 7-9h, and most preferably 8h; the temperature after the cooling is preferably 450-550℃, and more preferably 500℃.
[0061] In this invention, the first sintering is preferably carried out in an air atmosphere.
[0062] In the first heating stage, the moisture inside the material is removed, and pre-sintering is performed to prevent excessive shrinkage and cracking during later sintering. In the second heating stage, the green body is fully sintered and reaches the ideal density and strength. The present invention uses segmented heating to allow the ceramic to sinter better at different stages, and segmented cooling to prevent cracking when the ceramic cools down too quickly.
[0063] After obtaining the ceramic blank, the present invention performs a second sintering on the ceramic blank to obtain a yttrium oxide partially stabilized zirconia ceramic target.
[0064] Before the second sintering, the ceramic blank is preferably machined according to the present invention. The present invention utilizes machining to form the target shape of the target material.
[0065] In this invention, the temperature of the second sintering is preferably 800–1200°C, more preferably 900–1100°C, and even more preferably 1000°C; the holding time of the second sintering is preferably 2–5 h, more preferably 3–4 h; and the rate of heating to the temperature of the second sintering is preferably 50–100°C / h, more preferably 60–90°C / h, and even more preferably 70–80°C / h. In this invention, the second sintering is preferably carried out in an air atmosphere.
[0066] After the second sintering is completed, the present invention preferably cools the furnace to room temperature to obtain yttrium oxide partially stabilized zirconia ceramic target.
[0067] Figure 1 This is a flowchart illustrating the preparation method of the yttrium oxide partially stabilized zirconia ceramic target of the present invention. Figure 1 As shown, the present invention dries ZrO2 and Y2O3, then mixes and granulates them to obtain a first ceramic powder and a second ceramic powder respectively; the first ceramic powder and the second ceramic powder are mixed to obtain a multi-particle-size mixed powder; the multi-particle-size mixed powder is subjected to cold isostatic pressing to obtain a green body; the green body is subjected to a first sintering (i.e., high-temperature sintering) to obtain a ceramic body; the ceramic body is machined and finally subjected to a second sintering to obtain a yttrium oxide partially stabilized zirconia ceramic target.
[0068] The present invention provides a yttrium oxide partially stabilized zirconia ceramic target prepared by the preparation method described above.
[0069] This invention mixes two ceramic powders with different particle sizes, then cold isostatically presses and sintersects them, so that the smaller particle size powder is sandwiched between the larger particle size powder. This increases the bonding force of the powder and greatly reduces the closed pores in the target material, improving the stability of EB-PVD production, preventing abnormal phenomena, and greatly improving the coating performance.
[0070] This invention provides the application of the yttrium oxide partially stabilized zirconia ceramic target described above in the preparation of thermal barrier coatings by electron beam physical vapor deposition.
[0071] The following detailed description, in conjunction with embodiments, illustrates the yttrium oxide partially stabilized zirconia ceramic target, its preparation method, and its applications, but these should not be construed as limiting the scope of protection of this invention.
[0072] Example 1
[0073] 1) Weigh out 92wt% and 8wt% ZrO2 and Y2O3 with 99% purity respectively, and keep them at 120℃ for 12h.
[0074] 2) Mechanically mix the two raw materials for 6 hours;
[0075] 3) After granulation, the mixed powders were granulated to obtain powder particles with average particle sizes of 25 μm and 75 μm, respectively;
[0076] 4) Mix the two powders in a mass ratio of 2:1;
[0077] 5) The obtained multi-size mixed powder was pressed at 200 MPa for 300 s using a cold isostatic pressing equipment to obtain a green body;
[0078] 6) For high-temperature sintering of green bodies, a segmented heating and cooling method is adopted: the temperature is raised to 600℃ at a rate of 100℃ / h, held for 10h, then raised to 1400℃ at a rate of 100℃ / h, held for 10h, and then cooled to 500℃ at a rate of 100℃ / h. Finally, the temperature is cooled to room temperature with the furnace to obtain the ceramic body.
[0079] 7) The ceramic blank is machined to obtain an intermediate target material with dimensions of Φ68.5×200mm;
[0080] 8) The target material is heated to 900℃ at a rate of 100℃ / h, held at that temperature for 3h, and then cooled to room temperature in the furnace to obtain yttrium-stabilized zirconia ceramic target material.
[0081] After testing and analysis, the phase structure of the target material is mainly tetragonal, containing a small amount of monoclinic phase (such as...). Figure 2 (As shown); the target material purity is above 99.9%; the density is 4.1 g / cm³. 3 .
[0082] The target material of this embodiment was observed by SEM, and the results are as follows: Figure 3 As shown. By Figure 3 It can be seen that the target powder has a wide particle size distribution, high bulk density, large powder contact area, high overall density, and tighter bonding.
[0083] EB-PVD test was performed (experimental conditions: under a vacuum of 1×10⁻⁶). -2 ~4×10 -1 At a pressure of Pa, voltage of 19±1KV, and evaporation beam current of 0.6~1.05A, the target material operated stably without splashing, and no cracking occurred after the test (e.g., ...). Figure 4 (As shown).
[0084] Example 2
[0085] 1) Weigh out 94wt% and 6wt% ZrO2 and Y2O3 with 99% purity respectively, and keep them at 120℃ for 10h.
[0086] 2) Mechanically mix the two raw materials for 8 hours;
[0087] 3) After granulation, the mixed powders were granulated to obtain powder particles with average particle sizes of 25 μm and 75 μm, respectively;
[0088] 4) Mix the two powders in a mass ratio of 1:2;
[0089] 5) The obtained multi-size mixed powder was pressed at 200 MPa for 120 s using a cold isostatic pressing equipment to obtain a green body;
[0090] 6) For high-temperature sintering of green billets, a segmented heating and cooling method is adopted: heat up to 600℃ at a rate of 50℃ / h, hold for 10h, then heat up to 1600℃ at a rate of 50℃ / h, hold for 10h, then cool down to 500℃ at a rate of 50℃ / h, and finally cool down to room temperature with the furnace.
[0091] 7) The ceramic blank is machined to obtain an intermediate target material with dimensions of Φ68.5×200mm;
[0092] 8) The target material is heated to 900℃ at a rate of 50℃ / h, held at that temperature for 5h, and then cooled to room temperature in the furnace to obtain yttrium-stabilized zirconia ceramic target material.
[0093] After testing and analysis, the phase structure of the target material is mainly tetragonal, containing a small amount of monoclinic phase, such as... Figure 5 As shown; the target material purity is above 99.9%; the density is 4.3 g / cm³. 3 .
[0094] The obtained ceramic target material was observed by SEM, and the results are as follows: Figure 6 As shown. By Figure 6 It can be seen that the target powder has a wide particle size distribution, high bulk density, large powder contact area, high overall density, and tight bonding.
[0095] During EB-PVD testing, the target material operated stably without splashing, and no cracks appeared after the test. Figure 7 As shown.
[0096] Example 3
[0097] 1) Weigh out 92wt% and 8wt% ZrO2 and Y2O3 with 99% purity respectively, and keep them at 110℃ for 12h.
[0098] 2) Mechanically mix the two raw materials for 6 hours;
[0099] 3) After granulation, the mixed powders were granulated to obtain powder particles with average particle sizes of 10 μm and 80 μm, respectively;
[0100] 4) Mix the two powders in a mass ratio of 2:5;
[0101] 5) The obtained multi-size mixed powder was pressed at 150 MPa for 240 s using a cold isostatic pressing equipment to obtain a green body;
[0102] 6) For high-temperature sintering of green billets, a segmented heating and cooling method is adopted: heat up to 800℃ at a rate of 60℃ / h, hold for 6h, then heat up to 1300℃ at a rate of 60℃ / h, hold for 8h, cool down to 500℃ at a rate of 600℃ / h, and finally cool down to room temperature with the furnace.
[0103] 7) The ceramic blank is machined to obtain an intermediate target material with dimensions of Φ68.5×200mm;
[0104] 8) The target material is heated to 1100℃ at a rate of 60℃ / h, held at that temperature for 4h, and then cooled to room temperature in the furnace to obtain yttrium oxide partially stabilized zirconia ceramic target material.
[0105] After testing and analysis, the phase structure of the target material is mainly tetragonal, containing a small amount of monoclinic phase, such as... Figure 8 As shown; the target material purity is above 99.9%; the density is 4.4 g / cm³. 3 Electron microscopy images show that the powder has a wide particle size distribution, higher bulk density, greater density, and tighter binding (see...). Figure 9 ).
[0106] During the EB-PVD test, the target material operated stably without splashing, and no cracks appeared after the test (see...). Figure 10 ).
[0107] Comparative Example 1
[0108] 1) Weigh out 94wt% and 6wt% ZrO2 and Y2O3 with 99% purity respectively, and keep them at 120℃ for 10h.
[0109] 2) Mechanically mix the two raw materials for 8 hours;
[0110] 3) After granulation, the mixed powders yielded powder particles with an average particle size of 75 μm;
[0111] 4) The obtained powder was pressed at 200 MPa for 120 seconds using a cold isostatic pressing apparatus to obtain a green body;
[0112] 5) For high-temperature sintering of green billets, a segmented heating and cooling method is adopted: heat up to 600℃ at a rate of 50℃ / h, hold for 10h, then heat up to 1600℃ at a rate of 50℃ / h, hold for 10h, then cool down to 500℃ at a rate of 50℃ / h, and finally cool down to room temperature with the furnace.
[0113] 6) The ceramic blank is machined to obtain an intermediate target material with dimensions of Φ68.5×200mm;
[0114] 7) The target material is heated to 900℃ at a rate of 50℃ / h, held at that temperature for 5h, and then cooled to room temperature in the furnace to obtain yttrium-stabilized zirconia ceramic target material.
[0115] After testing and analysis, the purity of the target material is above 99.9%; the density is 4.0 g / cm³. 3 .
[0116] Electron microscopy images show that the powder particles have a relatively uniform size and low bulk density, resulting in low ceramic density and poor strength (see...). Figure 11 ).
[0117] During EB-PVD testing, the target material was unstable and cracked during operation (see...). Figure 12 ).
[0118] Comparative Example 2
[0119] 1) Weigh out 94wt% and 6wt% ZrO2 and Y2O3 with 99% purity respectively, and keep them at 120℃ for 10h.
[0120] 2) Mechanically mix the two raw materials for 8 hours;
[0121] 3) After granulation, the mixed powders yielded powder particles with an average particle size of 25 μm;
[0122] 4) The obtained powder was pressed at 200 MPa for 120 seconds using a cold isostatic pressing apparatus to obtain a green body;
[0123] 5) For high-temperature sintering of green billets, a segmented heating and cooling method is adopted: heat up to 600℃ at a rate of 50℃ / h, hold for 10h, then heat up to 1600℃ at a rate of 50℃ / h, hold for 10h, then cool down to 500℃ at a rate of 50℃ / h, and finally cool down to room temperature with the furnace.
[0124] 6) The ceramic blank is machined to obtain an intermediate target material with dimensions of Φ68.5×200mm;
[0125] 7) The target material is heated to 900℃ at a rate of 50℃ / h, held at that temperature for 5h, and then cooled to room temperature in the furnace to obtain yttrium-stabilized zirconia ceramic target material.
[0126] After testing and analysis, the purity of the target material is above 99.9%; the density is 4.6 g / cm³. 3 .
[0127] Electron microscopy images show that the powder particles are small in size and have an excessively high bulk density, making them unstable during EB-PVD experiments (see...). Figure 13 ).
[0128] During EB-PVD testing, the target material was unstable, exhibiting splashing and cracking during operation (see...). Figure 14 ).
[0129] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a yttrium oxide partially stabilized zirconia ceramic target, characterized in that, Includes the following steps: The mixed powder of ZrO2 and Y2O3 was granulated to obtain a first ceramic powder and a second ceramic powder, respectively; the average particle size of the first ceramic powder was 5~50μm; the average particle size of the second ceramic powder was 55~100μm. Furthermore, the difference between the average particle size of the second ceramic powder and the average particle size of the first ceramic powder is 50~80μm; The first ceramic powder and the second ceramic powder are mixed to obtain a multi-particle-size mixed powder; the mass ratio of the first ceramic powder to the second ceramic powder is (0.2~5):1; The multi-size mixed powder is subjected to cold isostatic pressing to obtain a green body; The green body is subjected to a first sintering to obtain a ceramic body; The ceramic blank is mechanically processed and then subjected to a second sintering to obtain a yttrium oxide partially stabilized zirconia ceramic target. The second sintering temperature is 800~1200℃, and the holding time is 2~5h.
2. The preparation method according to claim 1, characterized in that, The mass of ZrO2 is 92-94% of the total mass of ZrO2 and Y2O3.
3. The preparation method according to claim 1, characterized in that, The pressure of the cold isostatic pressing is 30~200MPa, and the holding time is 60~300s.
4. The preparation method according to claim 1, characterized in that, The first sintering process includes: first heating to 400~800℃, first holding for 6~10h, then heating to 1200~1600℃, second holding for 6~10h, cooling to 400~600℃, and finally cooling to room temperature with the furnace.
5. The preparation method according to claim 4, characterized in that, The rates of the first and second heating are independently 50~100℃ / h; the rate of cooling is 50~100℃ / h.
6. The yttrium oxide partially stabilized zirconia ceramic target prepared by the preparation method according to any one of claims 1 to 5.
7. The application of the yttrium oxide partially stabilized zirconia ceramic target as described in claim 6 in the preparation of thermal barrier coatings by electron beam physical vapor deposition.
Citation Information
Patent Citations
Heat stable formed ceramic, apparatus and method of using the same
CN102224120A
Preparation method of zirconium dioxide-yttrium oxide mixture ceramic target
CN103992109A